Character interrelationships and path analysis for yield components in MPOB-Senegal oil palm germplasm - Khin, Aye Myint; Mohd Din Amiruddin,; Mohd Y. Rafii,; Mohd Yusoff Abd Samad,; Shairul Izan Ramlee,; Zulkifli Yaakub,; Yusuff Oladosu, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Phenotypic associations among yield-related traits and the pattern of influence in crops are useful in evaluating, planning and selection criteria for the desirable traits. This research aimed to evaluate linear correlations and estimate the direct and indirect effects among morphological traits on oil yield of MPOB-Senegal germplasm. Data were collected annually for successive eight years (2000 to 2007) and was estimated for the phenotypic correlations, and decomposition into direct and indirect effects using path coefficient analysis. The result of the correlation and path coefficient analysis showed significant highly positive relations between some yield components and oil yield. Oil to wet mesocarp (OTWM) and bunch number (BNO) had high positive direct effect on oil yield while fresh fruit bunch (FFB), oil to fiber (OTF), fruit to bunch (FTB), and average bunch weight (ABWT) showed indirect effect on oil yield. In improvement of palm oil yield, traits that show high direct and/or indirect effect on oil yield should be considered. Hence, FFB, OTF, FTB, OTWM, and ABWT have maximum direct and indirect effect can be used effectively for the improvement of the palm oil yield of the MPOB-Senegal oil palm germplasm.